2019
DOI: 10.15381/anales.v80i4.17253
|View full text |Cite
|
Sign up to set email alerts
|

Obesidad severa en adolescentes peruanos: análisis de la Encuesta Nacional de Hogares (ENAHO), 2009-2010

Abstract: Introducción. La obesidad infantil es un problema de salud pública en nuestro país; sin embargo, la situación de la población entre 10 a 19 años ha sido poco estudiada. Objetivo. Determinar la prevalencia de obesidad y obesidad severa en adolescentes peruanos. Métodos. Estudio de datos secundarios provenientes de la Encuesta Nacional de Hogares 2009-2010. Se utilizó el índice de masa corporal (IMC) definiendo obesidad con un valor de IMC ≥ percentil 95 (p95). Obesidad severa (OS) mediante dos criterios: IMC ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Living in a rural region was also associated with higher obesity, contrary to Pajuelo Ramirez J et al [20] study, where urban dwellers had a higher risk. Chiroque Juárez et al [23] found that residing in urban areas resulted in 2.25 times more obesity than in rural areas.…”
Section: Factors Associated With Obesity By Bmi Wc and Whtrcontrasting
confidence: 72%
See 2 more Smart Citations
“…Living in a rural region was also associated with higher obesity, contrary to Pajuelo Ramirez J et al [20] study, where urban dwellers had a higher risk. Chiroque Juárez et al [23] found that residing in urban areas resulted in 2.25 times more obesity than in rural areas.…”
Section: Factors Associated With Obesity By Bmi Wc and Whtrcontrasting
confidence: 72%
“…Regarding the wealth index, wealth was associated with obesity, akin to Pajuelo et al [20] study in Peru, which revealed non-poverty status linked to obesity. However, our findings differ from Sigmund E et al [21], who reported that wealthier adolescents engage in more physical activity than those from lower-income backgrounds.…”
Section: Factors Associated With Obesity By Bmi Wc and Whtrmentioning
confidence: 82%
See 1 more Smart Citation